Cerebral hemodynamics comparison using transcranial doppler ultrasound and 4D flow MRI - Fico, Brandon G.; Miller, Kathleen B.; Rivera-Rivera, Leonardo A.; Corkery, Adam T.; Pearson, Andrew G.; Loggie, Nicole A.; Howery, Anna J.; Rowley, Howard A.; Johnson, Kevin M.; Johnson, Sterling C.; Wieben, Oliver; Barnes, Jill N. (Frontiers in Physiology, 2023)
Age-related changes in cerebral hemodynamics are controversial and discrepancies may be due to experimental techniques. As such, the purpose of this study was to compare cerebral hemodynamics measurements of the middle cerebral artery (MCA) between transcranial Doppler ultrasound (TCD) and four-dimensional flow MRI (4D flow MRI). Twenty young (25 ± 3 years) and 19 older (62 ± 6 years) participants underwent two randomized study visits to evaluate hemodynamics at baseline (normocapnia) and in response to stepped hypercapnia (4% CO2, and 6% CO2) using TCD and 4D flow MRI. Cerebral hemodynamic measures included MCA velocity, MCA flow, cerebral pulsatility index (PI) and cerebrovascular reactivity to hypercapnia. MCA flow was only assessed using 4D flow MRI. MCA velocity between the TCD and 4D flow MRI methods was positively correlated across the normocapnia and hypercapnia conditions (r=0.262; p=0.004). Additionally, cerebral PI was significantly correlated between TCD and 4D flow MRI across the conditions (r=0.236; p=0.010). However, there was no significant association between MCA velocity using TCD and MCA flow using 4D flow MRI across the conditions (r=0.079; p=0.397). When age-associated differences in cerebrovascular reactivity using conductance were compared using both methodologies, cerebrovascular reactivity was greater in young adults compared to older adults when using 4D flow MRI (2.11±1.68 ml/min/mmHg/mmHg vs. 0.78±1.68 ml/min/mmHg/mmHg; p=0.019), but not with TCD (0.88±1.01 cm/s/mmHg2 vs. 0.68±0.94 cm/s/mmHg2; p=0.513). In conclusion, our results demonstrated good agreement between the methods at measuring MCA velocity during normocapnia and in response to hypercapnia, but MCA velocity and MCA flow were not related. In addition, measurements using 4D flow MRI revealed effects of aging on cerebral hemodynamics that were not apparent using TCD.